2014
DOI: 10.7554/elife.02999
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ‘erasers’ for lysine crotonylated histone marks using a chemical proteomics approach

Abstract: Posttranslational modifications (PTMs) play a crucial role in a wide range of biological processes. Lysine crotonylation (Kcr) is a newly discovered histone PTM that is enriched at active gene promoters and potential enhancers in mammalian cell genomes. However, the cellular enzymes that regulate the addition and removal of Kcr are unknown, which has hindered further investigation of its cellular functions. Here we used a chemical proteomics approach to comprehensively profile 'eraser' enzymes that recognize a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
226
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 267 publications
(235 citation statements)
references
References 44 publications
5
226
3
1
Order By: Relevance
“…SIRT3 has been reported to interact with chromatin in U2OS cells, resulting in the repression of adjacent genes (68). Interestingly, SIRT3 KD leads to increased lysine crotonylation at five of seven genes analyzed in U2OS cells, along with a significant increase in mRNA levels of three candidate genes (10). These observations suggest that SIRT3 might repress the expression of target genes via modulation of histone lysine crotonylation.…”
Section: Fig 2 Subcellular Localization Of Mammalian Sirtuinsmentioning
confidence: 85%
See 2 more Smart Citations
“…SIRT3 has been reported to interact with chromatin in U2OS cells, resulting in the repression of adjacent genes (68). Interestingly, SIRT3 KD leads to increased lysine crotonylation at five of seven genes analyzed in U2OS cells, along with a significant increase in mRNA levels of three candidate genes (10). These observations suggest that SIRT3 might repress the expression of target genes via modulation of histone lysine crotonylation.…”
Section: Fig 2 Subcellular Localization Of Mammalian Sirtuinsmentioning
confidence: 85%
“…Tan et al described lysine crotonylation as novel histone PTM, which is specifically enriched at active gene promoters and potential enhancers in mammalian genome (155). A very recent study by Bao et al reported that SIRT3 possesses decrotonylase activity, using a similar catalytic mechanism as for acetyl lysine hydrolysis (10,36). siRNA-mediated SIRT3 FIG.…”
Section: Sirt3 Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Varying acyl moieties and sequence contexts of peptide linkers in the general probe scaffold 1 resulted in a broad set of sirtuin-probes (Figure 1a). [106][107][108] For instance, probe 1 was instrumental for identifying mitochondrial SIRT3 as key regulator of lysine-crotonylation ( Figure 1a). 106 An extension of this concept is the development of sirtuin substrates that also block NAD + binding and thereby prohibit the deacylation reaction.…”
Section: -105mentioning
confidence: 99%
“…[106][107][108] For instance, probe 1 was instrumental for identifying mitochondrial SIRT3 as key regulator of lysine-crotonylation ( Figure 1a). 106 An extension of this concept is the development of sirtuin substrates that also block NAD + binding and thereby prohibit the deacylation reaction. Peptides modified with bulky succinyl-lysines interact with the NAD + binding pocket and thereby inhibit the desuccinylase Sirt5.…”
Section: -105mentioning
confidence: 99%